IPTEKS LAPORAN KEUANGAN UNTUK MENILAI PROFITABILITAS DAN KINERJA PERUSAHAAN PT. ESTA GROUP JAYA - Sapetu, Martino; Kindangen, Wulan D (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. Esta Jaya Group is a private company located in Manad, with the construction company beingable to provide assistance in eradicating poverty and helping the goverments in terms of economic growth not only that but the linkages of the private sector that are able to prepare and also experts. In analyzing financial statements a company has things that must be considered in order to be a good and correct report so that it can be assessed. This can also be evidence of how far the company is able to create a profit and can be based into two categories, namely categories based on sales and based on investment. Keywords: accounting for financial statements, profitability, performance, analysis of financial statements, ratios